PENGARUH KONDISI FISIK RUMAH TERHADAP PENULARAN TB PARU PADA ANGGOTA KELUARGA (Studi Kasus di Wilayah Kerja Puskesmas Perak Timur Surabaya Tahun 2018) - Evi Nurdiana; Nur Haidah; AT Diana Nerawati (GEMA LINGKUNGAN KESEHATAN, 2018)
Tuberculosis is an infectious disease that caused by the bacterium Mycobacterium tuberculosis and more often infects lung organs than the other body organs . Healthy people at home with pulmonary TB sufferers are a group that is very susceptible to contracting the disease. One of possible factors that is at risk for pulmonary TB is the physical condition of the house which includes ventilation, occupancy, density, lighting, floor conditions, humidity, and temperature. The purpose of this study was to analyze the effect of the physical condition of the house on pulmonary TB transmission in the family members in the working area of Health Center East Perak Surabaya.This research is an observational analytic research with cross-sectional study design. The data collection is done by interviewing, observing, and measuring the physical condition of the house. The population in this study were 51 houses with pulmonary tuberculosis patients and a large sample of 45 houses with pulmonary TB patients. The data obtained were then analyzed analytically using Exact Fisher test.          The results of univariate analysis showed pulmonary tuberculosis transmission in family members (17.8%), the ventilation was unfullfilled the requirements (68.9%), lighting was unfullfilled the requirements (75.6%), the temperature was unfullfilled the requirements (68.9%) , humidity was unfullfilled the requirements (35.6%), floor conditions was unfullfilled the requirements (2.2%), and occupancy of density was unfullfilled the requirements (68.9%). The results of bivariate analysis showed that there was an influence on pulmonary TB transmission in family members, by the temperature (Pvalue = 0.007) and humidity (Pvalue = 0.017).The conclusion, the temperature and humidity affect the transmission of pulmonary TB in family members; ventilation, lighting, floor conditions, and occupancy of density do not affect the transmission of pulmonary TB in family members. It is recommended to do data collection and counseling about healthy homes and TB disease, treatment for all TB patients completely, and check family members immediately if they have symptoms of coughing for more than 2 weeks. Keywords      : Tuberculosis, family members, physical condition of the house.